Investigating the role of endocytosis in the uptake of photoassimilates in Gracilariopsis lemaneiformis (Rhodophyta) - Haihong Chen; Ziyan Shi; Hongxin Ji; Shengqi Ye; Xiaoqian Zhou; Zhijie dan; Xin Shen (BMC Plant Biology)
Abstract Background The translocation of photoassimilates is a critical process that links the source and sink in plants, playing an irreplaceable role in maintaining source-sink balance, ensuring plant growth and development, and the formation of yield. Nevertheless, the mechanisms underlying the translocation of photosynthetic products in macroalgae are yet to be fully understood. The purpose of this study is to reveal the role of endocytosis in the translocation of photosynthetic products in the marine red alga Gracilariopsis lemaneiformis by investigating the uptake of photosynthetic products by endocytosis and the impact of endocytic activity on cellular ultrastructure, photosynthesis, and growth. Results This study discovered that the endocytic activity in non-epidermal cells (NEC, sink cells) of G. lemaneiformis is significantly higher than that in epidermal cells (EC, source cells). NEC is capable of internalizing a greater amount of extracellular carbohydrates, such as sucrose, via endocytosis compared to EC. Further inhibition of endocytic activity in G. lemaneiformis using EIPA resulted in a significant reduction in the content of floridean starch within NEC, whereas the decrease in floridean starch content in EC was not statistically significant. Inhibition of endocytic activity led to an initial decline in photosynthetic efficiency of algal thalli within a few hours, which was followed by an increase as inhibition duration extended, yet the growth rate of the thalli remained substantially suppressed. Conclusions These findings indicate that endocytosis in G. lemaneiformis plays a role in regulating the cellular uptake of extracellular photoassimilates, which in turn influences the storage substances in sink cells and the overall growth and development of the algae. This study sheds new light on the regulatory mechanisms governing photoassimilate translocation in macroalgae.